Boron foliar applications in preventing deficiency and the mineral compositions of tomato plant - Magalhães, José Ronaldo; Monnerat, Pedro Henrique (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was conducted in greenhouse with nutrien solution to determine the effect of boron by foliar application in production of dry matter and nutrient uptake of tomato plant (Lycopersicum esculentum, Mill.). The experiment design was factorial 2 x 3, with two levels of boron in nutrient solution (270 and 1.08 ppb) and application of boric acid (H3BO3) at 1 g/liter at six and three days intervals, and boron application as a control. The symptoms of boron deficiency in the plant are described. The boron deficiency decreased the percentage of this element in the leaves and stem, and root was more retarded than above part of plant. The dry matter of roots increased proportionally more than stem and leaves by boron spray in the leaves, although the symptoms of boron deficiency in these parts of the plant did not disappear completely. The manganese was the element whose total amount absorbed was less affected by boron deficiency, and its concentration increased in all plant parts, more evidently in the roots.